Faktor-Faktor yang mempengaruhi Prestasi Belajar Santri Dayah Misbahudh Dhulam Al-Aziziyah Lueng Putu Pidie Jaya - Ulfah, Suhaili; Raihan, Iskandar; Hizbullah, Auliya (peusangan, 2024)
Student learning achievement is a necessity, to raise the status of the school and the success of teacher development in Islamic boarding schools. Many factors influence, but it is suspected that the dominant internal factors are discipline, learning motivation and student independence. This will be proven through research. This research is in the form of a survey using a questionnaire on 156 students in grades V and VI of Dayah Misbahudh Dhulam Al-Aziziyah Lueng Putu Pidie Jaya with a quantitative associative method. And data analysis using a path model. The results of the study found: 1) there is an influence of discipline, learning motivation and independence on student learning achievement both directly and indirectly, respectively by 47.71 percent, 37.57 percent and 37.06 percent. 2) Simultaneously, discipline, learning motivation and learning independence influence and contribute to learning achievement by 74,9 oersent. 3) there is a causal relationship between the variables of discipline, learning motivation and learning independence with a fairly close category.